Kastamonu-Taşköprü Orman Fidanlığında Üretilen 2+0 Yaşlı Karaçam Fidanlarının TSE Normlarına Göre Değerlendirilmesi - Avanoğlu, Birsel; Ayan, Sezgin; Demircioğlu, Nurcan; Sıvacıoğlu, Ahmet (SİGMA, Mühendislik ve Fen Bilimleri Dergisi, 2, 73–83, 2005)
In this study; 2+0 aged, bare rooted, Anatolian black pine seedlings, produced at Kastamonu–Taşköprü forest nursery by using four different seed origins were used. Some morphological characters of the seedlings were determined and the appropriateness to TS 2265/February 1988 and the more suitable standard to the EU norms named TS 2265/March 1976, were examined. In addition, the sensitiveness of quality classification of TSI for the seedlings were checked with discriminate analysis. According to the classifications of February 1988 and March 1976 standards, 85.5% and 62.7% of the investigated seedlings were determined as inconvenient seedlings, respectively. It was determined that the origin of Boyabat had the highest RCD (2.7 mm) and SH (15.7 cm) values among the four seed origins. For this reason, the using of this origin at dry and moist regions will be advisable. The February 1988 standard has the higher values than March 1976 standard from the point of the SH and S/R criteria. Nevertheless, a new standard suited to EU norms as to the RCD, should be developed. Bu çalışmada, Kastamonu-Taşköprü Orman Fidanlığında üretilen 2+0 yaşlı, çıplak köklü Pinus nigra Arnold. subsp. pallasiana (Lamb.) Holmboe. fidanları kullanılmıştır. Dört farklı tohum kaynağına ait olan bu fidanların bazı morfolojik karakterleri belirlenerek TS 2265/Şubat 1988 ve Avrupa Birliği (AB) normlarına uygun olan TS 2265/Mart 1976 kalite sınıflamasına uygunluğu irdelenmiştir. Ayrıca, söz konusu fidanlar için TSE kalite sınıflamasının hassasiyeti diskriminant analizleri ile denetlenmiştir. Taşköprü Orman Fidanlığı’nda yetiştirilen fidanların Şubat 1988 standartlarına göre; %85.5’i, Mart 1976 standartlarına göre %62.7’si elverişsiz (ıskarta) olduğu tespit edilmiştir. Dört tohum kaynağı içerisinde Boyabat tohum kaynağı, KBÇ (2.7 mm) ve FB (15.7 cm) bakımından en yüksek değerlere sahip olduğundan, gerek kurak gerekse nemli bölgelerde kullanımı daha doğru olabilecektir. Şubat 1988 standartları; FB, K kriterleri bakımından Mart 1976 standartlarına göre daha üstün değerlere sahiptir. Ancak, KBÇ kriteri bakımından AB normlarına uygun hale getirilerek yeni bir standardın geliştirilmesi uygun olacaktır.
EVALUATION OF TWO YEARS OLD SEEDLINGS OF THE ANATOLIAN BLACK PINE (Pinus nigra Arnold. subsp. pallasiana (Lamb.) Holmboe.) RAISED IN KASTAMONU-TASKOPRU FOREST NURSERY AS TO TSI QUALITY CLASSIFICATION
Keywords: Anadolu Karaçamı, TSE, Fidan, Kalite, Taşköprü, Morfoloji.; Anatolian Black Pine, TSI, Seedling, Quality, Taşköprü, Morphology.